A REVIEW ON THE SIGNIFICANCE OF NITYA VIRECHANA IN THE MANAGEMENT OF JALODARA (ASCITES) (International Journal of Ayurveda and Pharma Research, 2021)
Jalodara is a type of Udara roga. It is such type of a disease which is difficult to cure. Its occurrence is increasing day by day in our society. In Jalodara, there is accumulation of fluid in between Tvak and Mamsa of Udara pradesha (abdomen). As a result, there is distension of abdomen. Its main causes are Mandagni, Srota avarodha and Apa dosha etc. Here vitiated Kapha and Vata are mainly involved. In this disease accumulated Doshas are mainly obstruct the Swedavaha and Ambuvaha srotas. It has three stages which are Ajatodakavastha, Picchavastha and Jatodakavastha. Jalodara in its Jatodakavastha is incurable. It can be correlated with Ascites based on its clinical features. Ascites is the abnormal accumulation of free fluid in the peritoneal cavity. Its most common cause is portal hypertension related to hepatic cirrhosis. Ascites is asymptomatic when there is small accumulation of fluid in peritoneal cavity. But when there is larger accumulation of fluid (> 1 lit), it shows symptoms. In this article, Ayurvedic treatment principles for Jalodara have been discussed in details. These include Nidan parivarjana, Nitya virechana, therapies which remove the defects of liquid elements (Apam doshaharanam), Dipana and Shastra karma (abdominal tapping). This article is mainly based on the review of the significance of Nitya virechana in the management of Jalodara (Ascites).